2016
DOI: 10.1055/s-0036-1597846
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography for Verification of Endotracheal Tube Position in Neonates and Infants

Abstract: Ultrasonography (US) has been shown to be effective for verifying endotracheal tube (ETT) position in adults and older children but has been less studied in the neonates and infants. The literature regarding US utility for ETT positioning in this population is reviewed. A literature search was conducted using the EMBASE, Google Scholar, MEDLINE, Ovid, and Scopus databases with search terms regarding US relating to ETT intubation and positioning in neonates and infants. Nine relevant studies were included for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 18 publications
2
22
0
2
Order By: Relevance
“…In a randomised trial, Blayney et al 30 reported that a magnetically detectable ETT was superior to vocal cord guide in detecting ETT position. Ultrasound confirmation of ETT tip position was described by Slovis and Poland,31 and several studies show promising results 32 33. These and other methods of estimating ETT insertion depth, such as NTL, foot length34 and oro-helical length,35 require further evaluation.…”
Section: Discussionmentioning
confidence: 98%
“…In a randomised trial, Blayney et al 30 reported that a magnetically detectable ETT was superior to vocal cord guide in detecting ETT position. Ultrasound confirmation of ETT tip position was described by Slovis and Poland,31 and several studies show promising results 32 33. These and other methods of estimating ETT insertion depth, such as NTL, foot length34 and oro-helical length,35 require further evaluation.…”
Section: Discussionmentioning
confidence: 98%
“…Despite various proposed methods and technologies to guide endotracheal tube (ETT) depth in infants and children, [1][2][3][4][5] ETTs are frequently incorrectly positioned in this patient population, although there is a large variance in the proportion reported in the literature. 4,6 Chest radiography remains the standard of care for confirming appropriate ETT position within the trachea, which requires equipment and personnel to be brought to the bedside.…”
Section: Optoacoustic Evaluation Of Endotracheal Tube Depth In Pediatmentioning
confidence: 99%
“…A common standard of care practice for confirming ETT position is radiography. NICU patients undergo an average of over 10 radiographs per admission adding radiation exposure that has been linked to an increased long‐term risk of cancer and cognitive decline . Ultrasonography for ETT verification appears to be well tolerated in both the neonate and the pediatric population, and seems a helpful adjunct in determining proper ETT position in combination with other ETT verification modalities .…”
Section: Introductionmentioning
confidence: 99%
“…NICU patients undergo an average of over 10 radiographs per admission adding radiation exposure that has been linked to an increased long‐term risk of cancer and cognitive decline . Ultrasonography for ETT verification appears to be well tolerated in both the neonate and the pediatric population, and seems a helpful adjunct in determining proper ETT position in combination with other ETT verification modalities . This helps clinician comply with the Choosing Wisely campaign advocating against routine daily XR done solely to check ETT position in intubated infants .…”
Section: Introductionmentioning
confidence: 99%